Giant anomalous Hall effect in a ferromagnetic kagome-lattice semimetal - Liu, Enke; Sun, Yan; Kumar, Nitesh; Muechler, Lukas; Sun, Aili; Jiao, Lin; Yang, Shuo-Ying; Liu, Defa; Liang, Aiji; Xu, Qiunan; Kroder, Johannes; Suess, Vicky; et al. (Nature Physics, 2018)
Magnetic Weyl semimetals with broken time-reversal symmetry are expected to generate strong intrinsic anomalous Hall effects, due to their large Berry curvature. Here, we report a magnetic Weyl semimetal candidate, Co 3 Sn 2 S 2 , with a quasi-two-dimensional crystal structure consisting of stacked kagome lattices. This lattice provides an excellent platform for hosting exotic topological quantum states. We observe a negative magnetoresistance that is consistent with the chiral anomaly expected from the presence of Weyl fermions close to the Fermi level. The anomalous Hall conductivity is robust against both increased temperature and charge conductivity, which corroborates the intrinsic Berry-curvature mechanism in momentum space. Owing to the low carrier density in this material and the considerably enhanced Berry curvature from its band structure, the anomalous Hall conductivity and the anomalous Hall angle simultaneously reach 1,130 Ω −1 cm −1 and 20%, respectively, an order of magnitude larger than typical magnetic systems. Combining the kagome-lattice structure and the long-range out-of-plane ferromagnetic order of Co 3 Sn 2 S 2 , we expect that this material is an excellent candidate for observation of the quantum anomalous Hall state in the two-dimensional limit.
CRIS-Team Scopus Importer:2022-04-14